Clinical Research Advances in Congenital Heart Disease - Giordano, Raffaele; Cantinotti, Massimiliano (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Though the number of infants born with heart disease each year is relatively small (approximately 1% of the population), it is still a substantial issue worthy of investigation, which is why this Special Issue focuses on congenital heart disease in both children and adults. Advances in the treatment of such malformations have led to increased life spans for this population. Consequently, today, most patients treated for congenital heart disease are adults. The purpose of this Special Issue is to deal with the latest developments in the care of the fetus, infants and children, and how these patients should be treated, as well as to describe the results of follow-ups and the potential special needs of adults with congenital heart disease.